Ultrasound Imaging of the Deep Peroneal Nerve. (3rd September 2020) - Becciolini, Marco; Pivec, Christopher; Riegler, Georg
Abstract : Ultrasound is considered an excellent imaging modality to evaluate the nerves of the limbs. The deep peroneal nerve (DPN) is one of the terminal branches of the common peroneal nerve. The DPN may be affected by various disorders, which may be clinically challenging to show. This Pictorial Essay reviews the normal ultrasound anatomy of the DPN and presents disorders that may involve the nerve and its main branches along its course, from proximal to distal.